Spectrum-Effect Relationships of Flavonoids in Glycyrrhiza uralensis Fisch. - Tingting Li; Shiyao Hua; Jiahua Ma; Lin Dong; Fang Xu; Xueyan Fu (Journal of Analytical Methods in Chemistry)
Glycyrrhiza uralensis Fisch. is used in large quantities in traditional Chinese medicine. It contains flavonoids, saponins, and polysaccharides, with flavonoids being the main active ingredients. In this study, flavonoids were isolated from the roots of Glycyrrhiza uralensis Fisch. grown in 21 areas in China by water extraction, alcohol precipitation, polyamide resin separation, and other methods. Fingerprints were established by high performance liquid chromatography (HPLC). There were 15 common peaks in the fingerprints by similarity evaluations of the chromatographic fingerprints. The spectrum-effect relationships between the HPLC fingerprints and pharmacological activities of flavonoids in G. uralensis Fisch., including the heat clearing, detoxifying effects, cough relief, and phlegm elimination effects, were assessed by gray relational analysis and partial least squares regression. After HPLC-quadrupole time-of-flight mass spectrometry and standard comparison, these five identified compounds (liquiritin apioside, neoisoliquiritin, licochalcone A, licochalcone B, and licochalcone C) could be used to evaluate licorice quality with regard to its efficacy. This research provides a scientific basis for improving licorice quality and also establishes a model for modernization of traditional Chinese medicines.